Measuring the level of performance of country's cultural economics: The case of EU11 - Kristina Astikė; Viktorija Skvarciany (Amfiteatru Economic, 2024)
Culture itself forms society's identity, social values, and formal and informal social relations. This strengthens social capital, which is based on community, citizenship, volunteerism, and social values. These aspects promote effective democratic governance, and thereby ensure economic growth and, at the same time, the expansion of cultural economics. The main purpose of this article is to identify which of the selected cultural performance factors are more important in relation to each other and to create an index of cultural economics for the post-communist Central and Eastern European countries of the European Union according to these factors. The methods used in the article are as follows: analysis of scientific literature, qualitative expert interviews process with FAHP, and multi-criteria decision-making method TOPSIS. Two types of data were collected and analysed in the article: data received from the expert survey and existing statistical data. The results revealed that after creating an index of the post-communist Central and Eastern Europe countries of the European Union according to selected cultural performance factors, the first five places are occupied by Romania, Bulgaria, Slovakia, Latvia, and Lithuania. The practical implications of the research are that cultural economics is related to both the private and public sectors and, as a result, to their revenue; hence, the products it produces may be stated to contribute to the country's economy and development. The limitations of this study are statistics that have been used; the data is for 2020 as this is the most recent available.
Keywords: C83; D1; H1; Z1; 330; cultural economics; heritage; cultural institutions; EU11